PENERPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 7 PEMATANG PUDU KECAMATAN MANDAU KABUPATEN BENGKALIS - Hidayati, Elvita; Lazim N, Lazim N; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted because of the result of learning social study class III SDN 7 P.Pudu. From 30 Students who achieve KKm just 12 Students (40%) while students who didn’t complete 18 students (60%) with an average 67,66. The purpose of this research to inprove learning out comes IPS class III SDN 7 P.Pudu. with the application of learning models cooperative Snowball Throwing results obtained by the average value of 67,66 basic score in creased in the first cycle of 13,55% to 76,83 in the second cycle the average value of students also increased by 25,87% to 85,17 on the basic of completeness score IPS Student learning out comes is only 40% (finished). After the professor of applied learning model cooperative Snowball Throwing. In the first cycle classical completeness increased 73,3% (not finished), the second cycle of classical completeness obtained are increased to increased 93,3%. Activities of teacher at the first meeting of 58,3% with both categories. The second meeting increased to 79,1% in both categories. In the second cycle increased to 83,3% with the category very well. At a meeting of the second of the second cycle. The activities of teacher increased to 87,5% with the category very well. Activities of students in the first cycle of the fisrt meeting activity students acquire a percentage of 54,16% in both categories. The second meeting of the fisrt cycle to 70,3% inboth categories. At the first meeting of the second cycle of student activity increased to 83,3% with the category very well, and at the second meeting of the second cycle increased again to 91,6% with the category very well.Key Words : Snowbwll Throwing, learning outcomes IPS